2018
DOI: 10.1002/gps.5009
|View full text |Cite
|
Sign up to set email alerts
|

Regional brain volume reductions in major depressive disorder and bipolar disorder: An analysis by voxel‐based morphometry

Abstract: Objectives The present study investigated the usefulness of evaluating the existence of volume reduction in brain regions using voxel‐based morphometry (VBM) to dissociate major depressive disorder (MDD) from bipolar disorder (BD). Methods/Design This study enrolled 92 individuals with MDD, 32 individuals with BD, and 43 healthy controls (HCs). We focused on gray matter volume (GMV) of the subgenual anterior cingulate cortex (sgACC), subcallosal area (SCA), and hippocampus. The degree of volume reduction in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…Thus, adult rats who have experienced MD have reduced spatial learning and memory, suggesting that MD affects spatial memory in adulthood. This is in agreement with previous studies, though others have shown that the damage to learning and memory of MD rats only occurs in adulthood, or the spatial localization of MD rats is enhanced in the water maze . Increasing evidence shows that early life adverse events have profound long-lasting consequences in adult rats including neural, behavioral, and cognitive effects, , suggesting that the decreased spatial learning, memory, exploratory, and limbic activity in adult rats that we observed were caused by MD.…”
Section: Resultssupporting
confidence: 94%
“…Thus, adult rats who have experienced MD have reduced spatial learning and memory, suggesting that MD affects spatial memory in adulthood. This is in agreement with previous studies, though others have shown that the damage to learning and memory of MD rats only occurs in adulthood, or the spatial localization of MD rats is enhanced in the water maze . Increasing evidence shows that early life adverse events have profound long-lasting consequences in adult rats including neural, behavioral, and cognitive effects, , suggesting that the decreased spatial learning, memory, exploratory, and limbic activity in adult rats that we observed were caused by MD.…”
Section: Resultssupporting
confidence: 94%
“…234 Regarding the volume of brain regions associated with mood regulation and reward, some studies showed smaller amygdala and hippocampus and a larger striatum, although contrasting findings have also been found. [235][236][237][238] The integration of MRI with machine learning methods to distinguish between patients with BD and healthy controls, as well as for clinical stratification, was investigated by Mwangi et al, showing that the algorithm had up to 70% of accuracy and higher probability scores for those in the late-stage category (more than 10 total lifetime manic episodes including hospitalizations). 239 This potential impact of machine learning techniques in the evaluation of individuals with BD was extensively explored in a systematic review by Librenza-Garcia et al 240 Of 51 studies included, 38 applied machine learning to discriminate between BD and healthy controls or other psychiatric disorders, especially with neuroimaging data.…”
Section: Neuroimaging Findings In Bipolar Disordermentioning
confidence: 99%
“…MDD-related cortical thinning was found in orbitalfrontal cortex (Schmaal et al, 2017), medial prefrontal cortex (Treadway et al, 2015), temporal (Zhao et al, 2017), subgenual anterior cingulate cortex (Anderson et al, 2020), lingual gyrus (Suh et al, 2019), precentral (Bos et al, 2018) and par orbitalis (Merz et al, 2018) regions. Some studies also reported lower surface areas in lingual, fusiform, parahippocampal gyrii (Couvy-Duchesne et al, 2018) and subcallosal regions (Wei et al, 2020), as well as cortical volume reduction in prefronal cortex, orbitalfrontal cortex (Grieve et al, 2013), subcallosal regions (Wei et al, 2020), temporal pole, insula lobe (Amidfar et al, 2020) and subgenual anterior cingulate cortex (Niida et al, 2019). Although some research indicated MDD-related reduction in thalamus (Schmaal et al, 2016;Webb et al, 2014;Ye et al, 2020), amygdala (Qi et al, 2018) and hippocampus (Nugent et al, 2013), the MDD case-control volumetric differences in subcortical regions have been found to be insignificant in some other studies (Bos et al, 2018;Shen et al, 2017).…”
Section: Introductionmentioning
confidence: 98%